2013
DOI: 10.1371/journal.pone.0074192
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever in Humans and Animals in Mayotte, an Endemic Situation?

Abstract: Retrospective studies and surveillance on humans and animals revealed that Rift Valley Fever virus (RVFV) has been circulating on Mayotte for at least several years. A study was conducted in 2011 to estimate the seroprevalence of RVF in humans and in animals and to identify associated risk factors. Using a multistage cluster sampling method, 1420 individuals were enrolled in the human study, including 337 children aged 5 to 14 years. For the animal study, 198 seronegative ruminants from 33 randomly selected se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 20 publications
3
55
1
Order By: Relevance
“…; Lernout et al . ). The I 2 test result ( I 2 = 63.9%) suggested inconsistency in these studies' measures of association.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…; Lernout et al . ). The I 2 test result ( I 2 = 63.9%) suggested inconsistency in these studies' measures of association.…”
Section: Resultsmentioning
confidence: 97%
“…; Lernout et al . ) studies that investigated being male as a possible risk factor found a statistically significant association with RVF infection. ORs were available or able to be calculated for twelve of these thirteen studies, so twelve studies were included in a meta‐analysis (Jouan et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations